PENERJEMAHAN ISTILAH RELIGI: PENILAIAN KUALITAS KEAKURATAN - Yulianita, Nadia Gitya (Adabiyyāt: Jurnal Bahasa dan Sastra, 2017)
This paper aims to seek the category of religious terms in The Complete Idiot’s Guide to Understanding Islam (written by Emerick Yahiya), the translation’s techniques which are used to translate them, and the accuracy of the translation in Memahami Islam. The translation was done by Tim Penerjemah Pusat Bahasa dan Budaya Universitas Islam Negeri Syarif Hidayatullah. This research is a descriptive qualitative research and an embedded-case study. It was conducted by categorizing the religious terms which exist in the book. Based on the relevance theory, the researcher determined how a proper translation should be. Then, the researcher compared the source language and target language in order to identify the translation techniques. Finally, the researcher assessed the accuracy of the translation based on the translation techniques. The result shows that there are fourteen categories of religious terms in the book, namely eschatology, moral and ethical criteria, religious artifacts, religious constructions, religious events, religious groups, religious personages, religious sites, specialized religious activities, supernatural beings, terms of revelation, religious ceremonies, religious histories, and religious activities. In addition, the translator uses established equivalent, borrowing, literal, particularization, generalization, transposition, reduction, addition, explicitation and discursive creation techniques. In addition, the average score for the accuracy of the translation is 2,8.